Pengaruh Kemudahan Penggunaan, Pengalaman Pengguna dan Kepuasan Pelanggan, Terhadap Perilaku Pengguna Aplikasi E-commerce pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas 17 Agustus 1945 Surabaya. - Dwi Rijal Giri Prabowo; Ulfi Pristiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyses the effect of ease of use, user experience, and customer satisfaction on user behaviour of e-commerce applications for students of the Faculty of Economics and Business, Universitas 17 Agustus 1945 Surabaya. The method used is causal associative quantitative with data collection through questionnaires on 122 respondents. The results showed that the three variables had a significant effect on user behaviour. Ease of use (p = 0.026), user experience (p = 0.002), and customer satisfaction (p = 0.002) each have a positive influence on user behaviour. Simultaneously, these three factors also had a significant effect (Fcount = 25.059, p = 0.001). The findings support the theories of Technology Acceptance Model (TAM), Theory of Planned Behaviour (TPB), and Customer Experience Theory (CET). The practical implication is that app developers need to focus on easy-to-use design, pleasant user experience, and increased customer satisfaction to increase loyalty. This study has limitations in the sample of university students and the cross-sectional method which does not allow for long-term generalisation.